Cardiac responses to exercise in competitive child cyclists - Rowland, T.; Wehnert, M.; Miller, K. (Medicine & Science in Sports & Exercise, 2000)
Cardiovascular responses to exercise in highly trained child endurance athletes have not been well-defined. This study compared hemodynamic responses with progressive cycle exercise in seven competitive child cyclists (mean age 11.9 yr) compared with 39 age-matched untrained boys. Methods: Doppler echocardiography and gas exchange variables were utilized to assess cardiovascular changes during submaximal and maximal exercise. Results: Mean V(dot)O2max was 60.0 (±6.0) and 47.0 (±5.8) mL·kg-1·min-1 in the cyclists and nonathletes, respectively. At rest and maximal exercise, the cyclists demonstrated greater stroke index than the untrained subjects (resting mean 59 (±6) vs 44 (±9) mL·m-2; maximal mean 76 (±6) vs 60 (±11) mL·m-2), but the ratio of maximal:rest stroke index was similar in both groups (1.31 for cyclists, 1.41 for nonathletes). Both groups showed a plateau in stroke volume beyond low-intensity work levels. No significant difference was observed in maximal arteriovenous oxygen difference. Conclusions: These findings indicate that 1) maximal stroke volume is the critical determinant of the high V(dot)O2max in child cyclists and 2) factors that influence resting stroke volume are important in defining V(dot)O2max differences between child endurance athletes and untrained boys.